Peer Education on Adolescent Attitudes in Preventing Early Pregnancy in the Working Area of the Ibu Health Center, West Halmahera Regency - Reflin Mangengke; Reny Retnaningsih (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Early pregnancy among adolescents remains a significant public health problem and contributes to long-term medical, psychological, and social risks. Low knowledge and preventive attitudes towards reproductive health are among the factors contributing to the high rate of early pregnancy. This study aims to analyze the effect of peer education on adolescent attitudes towards early pregnancy prevention in the Ibu Community Health Center (Puskesmas Ibu) working area of West Halmahera Regency. The study design used a quasi-experimental approach with a pretest–posttest with a control group involving 40 respondents, consisting of 20 respondents in the intervention group and 20 respondents in the control group. The research instrument was an attitude questionnaire with a Likert scale that had undergone validity and reliability testing. Analysis was performed using the Wilcoxon test and the Mann–Whitney U Test at a significance level of 0.05. The results showed a significant increase in attitudes in the intervention group after receiving peer education, while the control group showed no significant change. Comparison of score changes between the two groups also showed a significant difference. These findings indicate that peer education is effective in improving adolescent attitudes towards early pregnancy prevention. This program is recommended as a community-based intervention strategy in primary health care and schools to support adolescent pregnancy prevention efforts.